2011
DOI: 10.1053/j.gastro.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Epithelial Stem Cells

Abstract: Advances in our understanding of stem cells in the gastrointestinal tract include the identification of molecular markers of stem and early progenitor cells in the small intestine. Although gastric epithelial stem cells have been localized, little is known about their molecular biology. Recent reports describe the use of inducible Cre recombinase activity to indelibly label candidate stem cells and their progeny in the distal stomach, (ie, the antrum and pylorus). No such lineage labeling of epithelial stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
177
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(180 citation statements)
references
References 91 publications
3
177
0
Order By: Relevance
“…Nevertheless, it appears that some Runx1-expressing cells are stem cells, whereas others are diferentiated cells, such as pit cells. Moreover, 80% of eR1 Additional markers have been proposed for gastric stem cells (e.g., DCKL1/DCAMKL1, CD133/PROM1, and CD44), but the multipotency of these cells has not yet been analyzed by lineage tracing [15,16]. Khurana et al found that CD44 (cluster of diferentiation 44) is mainly expressed at the base of antral/pyloric glands, in a region overlapping Lgr5, and in the isthmus region of the corpus glands [17,18].…”
Section: Discovery Of Gastric Stem Cells and Their Markersmentioning
confidence: 99%
“…Nevertheless, it appears that some Runx1-expressing cells are stem cells, whereas others are diferentiated cells, such as pit cells. Moreover, 80% of eR1 Additional markers have been proposed for gastric stem cells (e.g., DCKL1/DCAMKL1, CD133/PROM1, and CD44), but the multipotency of these cells has not yet been analyzed by lineage tracing [15,16]. Khurana et al found that CD44 (cluster of diferentiation 44) is mainly expressed at the base of antral/pyloric glands, in a region overlapping Lgr5, and in the isthmus region of the corpus glands [17,18].…”
Section: Discovery Of Gastric Stem Cells and Their Markersmentioning
confidence: 99%
“…Regulating the CSC microenvironmental niche SCs in normal gastric mucosa are thought to populate the proliferative zone in the neck-isthmus region [6,131]. Crypts in the stomach may act as niches for SCs, where surrounding structures and arising interactions contribute to the maintenance of stem/progenitor cell proliferation and differentiation [23,131].…”
Section: Abc Transportersmentioning
confidence: 99%
“…Crypts in the stomach may act as niches for SCs, where surrounding structures and arising interactions contribute to the maintenance of stem/progenitor cell proliferation and differentiation [23,131]. It has been suggested that CSCs reside only in designated conditioned compartments with an adequate cancer cell-stroma interface [23,132].…”
Section: Abc Transportersmentioning
confidence: 99%
“…Furthermore, it is becoming established that gastric units are monoclonal in origin [4]. Therefore, there is a consensus that all gastric epithelial cells originate from multi-potential stem or progenitor cells [5]. Indeed, lineage-tracing studies with chemical mutagenesis or Sox2 expression have demonstrated the existence of multi-potent stem cells in the rodent stomach [6,7].…”
mentioning
confidence: 99%
“…Previous studies have pinpointed the gland isthmus as the gastric stem cell zone, based on the abundant cellular proliferation and enrichment of immature, granule-free cells within the cycling population. Rare gastric stem cells in the isthmus presumably undergo transit amplification and contribute to the continuous bidirectional renewal of differentiated gastric epithelial cells [5,13]. Nevertheless, the marker genes and molecular characteristics of gastric stem cells are extremely elusive.…”
mentioning
confidence: 99%